Impact Stress in Water Resistance Voice Therapy: A Physical Modeling Study - Horáček, Jaromír; Radolf, Vojtěch; Laukkanen, Anne-Maria (Journal of voice, 2019)
OBJECTIVES: Phonation through a tube in water is used in voice therapy. This study investigates whether this exercise may increase mechanical loading on the vocal folds. STUDY DESIGN: This is an experimental modeling study. METHODS: A model with three-layer silicone vocal fold replica and a plexiglass, MK Plexi, Prague vocal tract set for the articulation of vowel [u:] was used. Impact stress (IS) was measured in three conditions: for [u:] (1) without a tube, (2) with a silicon Lax Vox tube (35 cm in length, 1 cm in inner diameter) immersed 2 cm in water, and (3) with the tube immersed 10 cm in water. Subglottic pressure and airflow ranges were selected to correspond to those reported in normal human phonation. RESULTS: Phonation threshold pressure was lower for phonation into water compared with [u:] without a tube. IS increased with the airflow rate. IS measured in the range of subglottic pressure, which corresponds to measurements in humans, was highest for vowel [u:] without a tube and lower with the tube in water. CONCLUSIONS: Even though the model and humans cannot be directly compared, for instance due to differences in vocal tract wall properties, the results suggest that IS is not likely to increase harmfully in water resistance therapy. However, there may be other effects related to it, possibly causing symptoms of vocal fatigue (eg, increased activity in the adductors or high amplitudes of oral pressure variation probably capable of increasing stress in the vocal fold). These need to be studied further, especially for cases where the water bubbling frequency is close to the acoustical-mechanical resonance and at the same time the fundamental phonation frequency is near the first formant frequency of the system.
Keywords: hlasové řasy; hlasový trénink; Voice Training; křemík; Silicon; polymethylmethakrylát; lidé; tlak; Vocal Cords; mechanický stres; Stress, Mechanical; Phonation; Polymethyl Methacrylate; anatomické modely; fonace; Voice Quality; kvalita hlasu; Models, Anatomic; Pressure; Humans